Papua Ethnic Forestry and Agricultural Utilization Study - Triyoso, Anang; Sumbono, Aung (AMCA Journal of Community Development, 2024)
Papua Island has extensive forests and agricultural land. Forestry and agriculture on the Indonesian island of Papua have been partially utilized, but the optimization of utilization so that it has added value has not been fully worked out so that there is a need for a special study of this problem. This paper aims to reveal the facts of the suboptimal utilization of forestry and agriculture in Papua. This study adopts a case study based on the results of official government reports and related research results that have been published. Papua in this study is the island of Papua which is included in the territory of the Republic of Indonesia. The analysis was carried out using the SWOT method and discussed descriptively based on the findings obtained. The results of the study show that forestry utilization is only limited to wood. Exploitation of Papuan forest wood is carried out and traded as raw materials, other forest assets have not been cultivated or worked on but are not well organized. Meanwhile, the agricultural products that are traded are not the typical agricultural crops native to Papua. This situation has an impact on trade values that do not benefit the indigenous Papuans.